1989
DOI: 10.2134/agronj1989.00021962008100010018x
|View full text |Cite
|
Sign up to set email alerts
|

Leaf Water Potential, Relative Water Content, and Diffusive Resistance as Screening Techniques for Drought Resistance in Barley

Abstract: Rapid drought resistance screening techniques could accelerate selection of improved cultivars for semiarid areas. This study was conducted to determine if total leaf water potential, leaf relative water content, and leaf diffusive resistance could be used to differentiate between barley (Hordeum vulgare L.) cultivars differing in apparent drought resistance. Resistant and susceptible cultivars were selected by regressing individual cultivar yields against site mean yield for numerous yield trials. Individual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
87
0
4

Year Published

1995
1995
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(95 citation statements)
references
References 21 publications
(29 reference statements)
4
87
0
4
Order By: Relevance
“…Following the LT measurements, leaf disks (1.3 cm diameter each) were collected with a cork borer from the same leaves used for F v /F m , SPAD index and LT measurements and used to determine leaf relative water content (RWC) following the method of Matin et al (1989). Five disks per plant were collected, immediately sealed in glass vials and quickly transported to the laboratory in an ice-cooled chest.…”
Section: Methodsmentioning
confidence: 99%
“…Following the LT measurements, leaf disks (1.3 cm diameter each) were collected with a cork borer from the same leaves used for F v /F m , SPAD index and LT measurements and used to determine leaf relative water content (RWC) following the method of Matin et al (1989). Five disks per plant were collected, immediately sealed in glass vials and quickly transported to the laboratory in an ice-cooled chest.…”
Section: Methodsmentioning
confidence: 99%
“…Key antioxidant enzymes, including APX (EC 1.11.1.11) and CAT (EC 1.11.1.6), were assayed exactly as described by Pompelli et al (2010a). Chl and total carotenoids were extracted using 80% (v/v) aqueous acetone and quantified spectrophotometrically, according to Lichtenthaler, in 1987. Leaf disks (each 1.3 cm in diameter) were collected with a cork borer from the same leaves used for P N measurements and were used to determine the leaf relative water content (RWC), based on the method of Matin et al (1989), with some modifications. Five disks per plant were collected immediately sealed in glass vials and quickly transported to the laboratory in an ice-cooled chest.…”
Section: Biochemical Measurementsmentioning
confidence: 99%
“…Then, the disks were quickly and carefully blotted dry with lint-free tissue paper before determining the turgid weights. Dry weights were recorded after drying the leaf samples in an oven for 48 hours at 80ºC (Matin et al, 1989).…”
Section: Biochemical Measurementsmentioning
confidence: 99%
“…Among testers, the line 9451 have highest positive GCA effects of 0.49 closely followed by the tester line 9437 (0.34) which is desirable under normal and drought conditions. Seropian andPlanchon, andMatin et al 1989 who also worked on combiningabilitz and reported similar findings. .…”
Section: Ltr X Trmentioning
confidence: 62%
“…Assessment of genotypes for drought resistance on the basis of combining ability estimates for leaf and other physiological attributes, play a vital role in water relations of wheat under different sowing regimes (Seropian, C. and C. Planchon. 1984;Matin et al 1989). The knowledge of general combining ability (GCA) provided an estimation of degree of additive gene action and specific combining ability (SCA) exhibited the performance of two particular varieties/lines in a specific cross, which would reflect non-additive type of gene action (Phoelman, J.M.…”
Section: Introductionmentioning
confidence: 99%